Decidual stromal cells support tolerance at the human foetal-maternal interface by inducing regulatory M2 macrophages and regulatory T-cells. (August 2021) - Lindau, R.; Vondra, S.; Spreckels, J.; Solders, M.; Svensson-Arvelund, J.; Berg, G.; Pollheimer, J.; Kaipe, H.; Jenmalm, M.C.; Ernerudh, J.
Graphical abstract: Highlights: Decidual stromal cells induce and promote survival of decidual-type macrophages. Decidual stomal cells induce regulatory T-cells in a paracrine manner. Both 1 st trimester and term stromal cells possess these immune regulatory abilities. Protein profiling supports prominent regulatory functions of decidual stromal cells. Decidual stromal cells may initiate and support fetal-maternal immune tolerance. Abstract: During pregnancy, the semi-allogeneic nature of the foetus requires maternal immune adaption and acquisition of tolerance at the foetal-maternal interface. Macrophages with regulatory properties and regulatory T (Treg) cells are central in promoting foetal tolerance and are enriched in the decidua (the uterine endometrium during pregnancy). Although tissue-resident decidual stromal cells (DSC) have been implicated in regulatory functions, it is not known if they are able to induce the regulatory phenotype of macrophages and T-cells. In this study we report that maternally derived DSC are able to induce homeostatic M2 macrophages and Treg cells. CD14 + monocytes and CD4 + T-cells from healthy non-pregnant women were cultured in the presence or absence of conditioned medium (CM) from DSC isolated from 1 st trimester and term placentas. DSC-CM alone was able to promote the survival of macrophages and to induce a regulatory CD14 bright CD163 + CD209 + CD86 dim phenotype, typical for decidual macrophages and similar to that induced by M-CSF. Interestingly, DSC-CM was also able to overrule the pro-inflammatory effects of GM-CSF by upregulating CD14, CD163 and CD209. Protein-profiling showed that M-CSF was secreted by DSC, and blocking of M-CSF partially reversed the M2 phenotype and reduced viability. DSC-CM also expanded CD25 bright Foxp3 + Treg cells, an expansion that was abolished by a SMAD3-inhibitor, indicating the contribution of TGF-β signaling. In conclusion, our findings collectively emphasize the role of tissue-resident stromal cells in shaping the tolerogenic environment at the foetal-maternal interface.